PENGGUNAAN WHATSAPP GROUP SEBAGAI SARANA PEMBELAJARAN JARAK JAUH DI SD NEGERI TAMBAKSARI - Admi Isni Rifanisari; Badarudin Badarudin (Khazanah Pendidikan, 2021)
This study aims to analyze and describe learning activities using WhatsApp Group as a means of distance learning at SD Negeri Tambaksari and its obstacles. This research was conducted using a descriptive qualitative approach conducted by interviewing participants, namely teachers, guardians of students and students. The results showed that low-class teachers opened learning with greetings and high-class teachers did not open learning, material in high and low classes covered all subjects but did not fulfil all learning outcomes, the method used by low and high-class teachers was the assignment method. , the media used by low-class teachers and high-class teachers is a photo feature, assessments conducted by low-class teachers and high-class teachers in the form of online and portfolio based tests, low-class teachers and high-class teachers do not reflect, low-class teachers close learning with giving messages to students and closing greetings while high-class teachers did not close the lesson. The obstacles for teachers in learning using WhatsApp Group include limited quota, limited cellphone storage for guardians of students, teachers find it difficult to determine the method, assignments were given by the teacher through WhatsApp Group make students lazy.